How to write a guideline from start to finish a handbook for healthcare professionals - Bowker, Richard; Douglas, Hannah-Rose (Elsevier/Churchill Livingstone, 2008)
Guidelines are an integral part of modern health care systems and are used and developed by health care professionals such as doctors, nurses and therapists. This book provides a handbook for health professionals on the process of Guidelines preparation and implementation. It includes many real-life examples of each step in the process.